Bootstrap Methods To Evaluate The Efficiency Of The Estimators Of The Spatial Unilateral AR(1,1) Model - Siregar, Latifah Rahayu (2011)
Three categories of the spatial data are geostatistical data, lattice data and point pattern data. This thesis focuses on the estimation aspect of the spatial unilateral autoregressive models for spatial lattice data on two-dimensional regular grid. Specifically, this thesis evaluate the efficiency of the estimators of the first order spatial unilateral autoregressive model, AR(1,1) using the bootstrapping methods. A comparative studies are done to compare the performance among the available methods for estimating the parameters of AR(1,1) model, namely the Yule- Walker, the unbiased Yule-Walker, the least squares and the maximum likelihood methods.